Research on vehicle controller and control strategy for pure electric vehicle with composite power. (26th May 2019) - Zhou, Meilan; Wang, Jiaming; Chen, Qilong
Vehicle control unit (VCU) is the centre of the whole vehicle control system. Its control performance directly affects the overall control effect of the vehicle. The vehicle controller of a pure electric vehicle with composite power is taken as the research object. The composition of the vehicle control system and principle of operation are analysed, the energy management control strategy of composite power based on fuzzy control is formulated, the CRUISE software is used to build the vehicle model of pure electric vehicle with compound power supply, and the simulation results show that the fuzzy control strategy is effective under the condition of urban road in China. The experimental platform of the vehicle control system is built. Experimental results show that the energy management strategy of compound power supply is effective and feasible.